2023
DOI: 10.3390/insects14010050
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of the Sodium/Potassium ATPase Subunit Beta 2 Reduces Egg Production in the Dengue Vector, Aedes aegypti

Abstract: The Na+/K+ ATPase (NKA) is present in the cellular membrane of most eukaryotic cells. It utilizes energy released by ATP hydrolysis to pump sodium ions out of the cell and potassium ions into the cell, which establishes and controls ion gradients. Functional NKA pumps consist of three subunits, alpha, beta, and FXYD. The alpha subunit serves as the catalytic subunit while the beta and FXYD subunits regulate the proper folding and localization, and ion affinity of the alpha subunit, respectively. Here we demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…Our previous study on the CAT1 and GCN1 interaction showed that GCN1 knockdown affected mosquito fecundity but did not affect vitellogenin expression [35]. Earlier knockdown studies of proteins associated with the mTOR signaling pathway and A. aegypti CATs often resulted in a reduction in egg numbers but never total sterility [57,59,60,76]. P1 knockdown also caused a significant reduction in the survival of female mosquitoes; in contrast, knockdown of GCN1 did not cause any mortality.…”
Section: Discussionmentioning
confidence: 96%
“…Our previous study on the CAT1 and GCN1 interaction showed that GCN1 knockdown affected mosquito fecundity but did not affect vitellogenin expression [35]. Earlier knockdown studies of proteins associated with the mTOR signaling pathway and A. aegypti CATs often resulted in a reduction in egg numbers but never total sterility [57,59,60,76]. P1 knockdown also caused a significant reduction in the survival of female mosquitoes; in contrast, knockdown of GCN1 did not cause any mortality.…”
Section: Discussionmentioning
confidence: 96%